The Mediating Role of Satisfaction in the Impact of Complaint Handling and Service Quality on Loyalty of Independent BPJS Health Participants - Desi Oktarina; Renil Septiano; Laynita Sari; Marwan Marwan; Lusiana Lusiana (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to examine the influence of complaint handling and service quality on the loyalty of independent BPJS Health participants, with participant satisfaction acting as a mediating variable. A quantitative approach was employed using the SEM-PLS method, involving 251 respondents in Sijunjung Regency. The findings reveal that both complaint handling and service quality positively affect participant satisfaction. However, complaint handling has a negative impact on loyalty, indicating that negative experiences continue to influence participants even after their complaints are addressed. Meanwhile, satisfaction significantly mediates the relationship between service quality and participant loyalty.